Analysis of Project Implementation Costs Using the Crashing Method in The Improvement of The Andongrejo-Bandialet Road, Jember District - Ardianto, Lukman; Wulandari, Esti; Witjaksana, Budi (International Journal Labs, 2025)
Construction project control is a systematic process aimed at ensuring that project objectives align with planning standards. One method used to accelerate project duration is